Evaluating a Comprehensive Toolkit for Journal Editors and Publishers: Insights from Nepal and Developing Nations - Shankar, Pathiyil Ravi; Amgain, Kapil (Journal of Karnali Academy of Health Sciences, 2026)
The Coalition for Diversity and Inclusion in Scholarly Publishing (C4DISC) has published a focused toolkit to promote diversity, equity, inclusion, and accessibility (DEIA) in scientific publications and help editors and publishers create a more inclusive and equitable publishing environment. The online toolkit has several sections. Among the recommendations are developing an inclusive culture and mission, collecting and reporting demographic data of authors, reviewers and editors using inclusive terminology, recruiting broadly and internationally for the positions of journal editors, board members and reviewers, train and mentor peer reviewers, and fostering equity in peer review. Many recommendations can be easily adopted by journals while some others may be more challenging. Despite its limitations, the toolkit is a good first initiative to promote DEIA in academic publishing.